2020
DOI: 10.1093/mnras/staa497
|View full text |Cite
|
Sign up to set email alerts
|

MHD-shock structures of astrospheres: λ Cephei -like astrospheres

Abstract: The interpretation of recent observations of bow shocks around O-stars and the creation of corresponding models require a detailed understanding of the associated (magneto-)hydrodynamic structures. We base our study on three-dimensional numerical (magneto-)hydrodynamical models, which are analyzed using the dynamically relevant parameters, in particular, the (magneto)sonic Mach numbers. The analytic Rankine-Hugoniot relation for HD and MHD are compared with those obtained by the numerical model. In that contex… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 54 publications
(97 reference statements)
2
35
0
Order By: Relevance
“…Thus, for successful application of cold plasma technology it is important to not only understand interactions at the bio-plasma interface during treatment, but also to understand the short-term and long-term consequences of plasma induced biomolecule alteration and the effect this may have on biochemical processes. In fact, plasma induced chemical modification of proteins and amino acids [19,20] and lipids [21] have been studied in isolation. Additionally, both simulated, modeling studies and direct experimentation have shown how interactions of cold plasma chemical species modify amino acids [22,23], change protein structure and function [19,[24][25][26] and oxidize lipids [27,28] but these studies are limited in their ability to examine or understand the long-term biological effects of the plasma induced modifications in a complex biosystem.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, for successful application of cold plasma technology it is important to not only understand interactions at the bio-plasma interface during treatment, but also to understand the short-term and long-term consequences of plasma induced biomolecule alteration and the effect this may have on biochemical processes. In fact, plasma induced chemical modification of proteins and amino acids [19,20] and lipids [21] have been studied in isolation. Additionally, both simulated, modeling studies and direct experimentation have shown how interactions of cold plasma chemical species modify amino acids [22,23], change protein structure and function [19,[24][25][26] and oxidize lipids [27,28] but these studies are limited in their ability to examine or understand the long-term biological effects of the plasma induced modifications in a complex biosystem.…”
Section: Introductionmentioning
confidence: 99%
“…Such correlations are implicit to the index κ and indicate strong nonlinear couplings, which are provided by interaction potentials which are mediated not by collisions but by excitation of waves. It is thus not surprising if κ-distributions are found in turbulent dilute high temperature plasmas like the solar wind [28], near collisionless shock waves [29], Earth's bow shock [30], the magnetosheath [31], at the boundaries of the heliosphere and astrospheres [32], where various types of waves can be excited as both, eigenmodes or sidebands, which even occupy the evanescent branches of the dielectric response function causing a continuous almost featureless power spectrum of fluctuations, which is typical for well-developed turbulence. One may, therefore, expect that the statistical mechanics underlying well-developed collisionless turbulence will become kind of Olbert-Lorentzian in terms of the probability distribution.…”
Section: Discussionmentioning
confidence: 99%
“…However, we can use the known density structure of astrospheres, which is similar to the hydrostatic case. From some distance r s,0 above the star's surface up to the termination shock, the density follows an inverse-square law (e.g., Scherer et al 2020). Following our deliberations in Sect.…”
Section: Appendix A: the Astrosphere Of Rgb Starsmentioning
confidence: 97%